PEMANFAATAN IKAN BARAKUDA PADA PEMBUATAN BATAGOR (BASO TAHU GORENG) - M. Supriyono; Sukriadi, Erie Hidayat (JURNAL MANAJEMEN KULINER, 2022)
Batagor is a typical food originating from Bandung, West Java, with the main ingredient being mackerel fish, but in this study it was developed to be able to make product innovations, namely mackerel fish meat instead of barracuda fish meat. The purpose of this study was to determine the taste, aroma, texture and color of batagor barracuda fish, the method used in this study was an experiment using an organoleptic test on a sample of 33 people as respondents. The results of this study indicate that the taste produced from batagor barracuda fish is delicious to enjoy, but the aroma still smells fishy, while the texture and color are in accordance with the expected napa, namely the texture is chewy and soft, with a brownish yellow color after frying.